The “The benefits of wordwall games for teaching and learning Mandarin language - Kariyati, Ani Kariyati; ., Syahrul; ., Mukhaiyar (Bambuti, 2024)
This article aims to discuss the application of the benefits of the worldwall game as an innovative learning alternative for Mandarin language subjects. In the digital era, the integration of technology in learning is becoming increasingly important to increase student engagement and learning outcomes. One tool that stands out in the context of learning Mandarin is wordwall, a game-based learning platform that provides various interactive activities. This article aims to explain and evaluate the benefits of using wordwalls in the context of Chinese language teaching and learning. The implementation of online learning is still experiencing problems, especially students' enthusiasm for learning has decreased. To overcome this obstacle, one interesting way to increase student enthusiasm for learning is to use the wordwall game. This wordwall game is an online learning media (E-Learning) which has game, quiz, discussion and survey features. This research examines the wordwall game which has the benefit of being an effective learning medium to increase students' mastery and motivation in learning Mandarin online. Quantitative research with an experimental approach, with a pre-test and post-test design with a control group and an experimental group. Population took 60 students taking MKU Mandarin courses, divided into 2 groups, namely the control group and the experimental group. Data collection for this research used a language mastery test instrument to measure the ability of four aspects of language, namely listening, speaking, reading and writing. To measure the level of student motivation, a questionnaire technique using Google Forms was used. The independent variable is the use of the wordwall game as a learning medium. Mastery of Mandarin and student motivation are the dependent variables. The results of research on learning with wordwall make the learning process easy, fun and can help students understand Mandarin. Apart from that, learning by applying playing techniques using wordwall games is very appropriate for beginner Mandarin learners.